Relative concerns of rural-to-urban migrants in China - Alpaslan Akay; Olivier Bargain; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2011)
As their environment changes, migrants constitute an interesting group to study the effect of relative income on subjective well-being. This paper focuses on the huge population of rural-to-urban migrants in China. Using a novel dataset, we find that the well-being of migrants depends on several reference groups: it is negatively affected by the income of other migrants and workers of home regions; in contrast, we identify a positive, signal effect vis-à-vis urban workers: larger urban incomes indicate higher income prospects for the migrants. These effects are particularly strong for migrants who wish to settle permanently, decline with years since migrations and change with other characteristics including work conditions and community ties.
urn:nbn:de:101:1-201104113533
Keywords: C90; D63; 330; China; relative concerns; well-being; Landflucht; Binnenwanderung; Nutzen; Zufriedenheit; China